Optimization Engine for the FlexTools Design Space Exploration Platform - Alipour, Salar; Hidaji, Babak (My University, 2011)
A general-purpose datapath interconnect is designed to make the processor efficient in executing a wide array of diverse applications. An embedded processor, typically working with a limited application domain, does not necessarily utilize the fixed, general-purpose datapath interconnect efficiently. If we consider the interconnect to be a flexible resource, the datapath can be fine tuned to one or a few applications. The addition of an interconnect link between two datapath units has the potential to reduce execution time, while the removal of an unused link can save area and power dissipation. Finding the most energy-efficient datapath interconnect configuration for a software application domain is a time-consuming process, since it involves rescheduling of the targeted application(s) on different datapath implementations. We present an automated optimization engine that is based on a genetic algorithm. This engine aids the designer in finding the most energy-efficient interconnect configuration of a simple processor datapath. We show that an optimized datapath interconnect can offer an energy saving of 38% with respect to a general-purpose datapath reference, if the interconnect links are matched to the need of one application.
Keywords: Datorteknik; Computer Engineering